The Acceptance of Augmented Reality’s Role in Elevating Customer Attitude within Malaysia’s Local Fashion Merchandising - Ibrahim, Nadhrathul Ain; Chen, Tan Yi; Ahmad, Nur Hidayah; Antara, Purnomo M.; Beta, Mayang Delima Mohd; Musa, Rosidah (Advances in Social Sciences Research Journal, 2024)
The adoption of augmented reality has recently developed as a popular approach for conducting digital business via virtual try-ons, virtual fitting rooms, online shopping apps, and digital wardrobes. Retailers are switching from traditional online shopping to a more interactive strategy, drawn by the usefulness of augmented reality. This research intends to investigate the impact of attributes such as interaction, vividness, and novelty on perceived usefulness and perceived ease of use, impacting customer attitudes towards using augmented reality in online fashion buying. Using the Technology Acceptance Model (TAM) framework, the study demonstrates that all of these features have a significant effect on perceived usefulness and perceived ease of use, influencing buyers to accept augmented reality on virtual try-ons, virtual fitting rooms, online shopping apps and digital wardrobe in their online fashion shopping experiences.